Neuroplasticity of the white matter tracts underlying recovery of diarrhea-predominant irritable bowel syndrome following acupuncture treatment - Li, Jing; Ng, WingYi; Liu, YongKang; Fang, XiaoKun; Wang, ZhongQiu; Pei, LiXia; Wei, XueHu (Frontiers in Neuroscience, 2024)
Irritable bowel syndrome (IBS) is a functional bowel disorder frequently associated with other pain syndromes and psychiatric conditions, including depression and anxiety. These abnormalities coincide with alterations in the brain’s structure, particularly in the thalamus and cingulate system. Acupuncture has been demonstrated to be highly effective in treating IBS. However, it remains unclear how white matter (WM) tracts change after acupuncture treatment, and whether the neuroplasticity of these tracts can serve as a neural marker to assist in the development of novel treatments. In this study, we aim to answer these questions by investigating longitudinal changes in the WM of the thalamus and cingulate system in a group of diarrhea-predominant irritable bowel syndrome (IBS-D) patients before and after acupuncture treatment. We found that after acupuncture treatment, as IBS symptoms improved, there were significant changes in the microstructure of the right thalamus radiation (TR) (p < 0.05) and the right cingulum hippocampus (CH) (p < 0.05). At the same time, patients with reduced IBS symptom severity scores (SSSs) were associated with the change of the right CH (p = 0.015, r = −0.491), while reduced depressive conditions correlated with the change of the left TR (p = 0.019, r = 0.418). In addition, the consequences for the quality of life (QOL) showed a correlation with the right cingulum [cingulate cortex (CC)] (p = 0.012, r = 0.504) and left TR (p = 0.027, r = −0.397). Our study highlighted the potential implications of neuroplasticity in WM tracts for IBS. Furthermore, these findings suggested that the right CH, TR, and right CC can serve as potential “biomarkers” of IBS-D recovery under acupuncture treatments.